2007
DOI: 10.1590/s0102-311x2007000900010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação transcultural para o Brasil do instrumento Caregiver Abuse Screen (CASE) para detecção de violência de cuidadores contra idosos

Abstract: Este artigo descreve a primeira parte da adaptação transcultural da versão em português, para o Brasil, do Caregiver Abuse Screen (CASE), um instrumento simplificado para suspeição de violência contra o idoso. O CASE foi originalmente desenvolvido no Canadá e utilizado para rastrear violências em idosos entrevistando seus cuidadores. O processo de avaliação de equivalências conceitual e de itens, que envolveu uma ampla e sistemática revisão bibliográfica, consistiu de uma discussão em grupo de expertos. A equi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
0
7
0
7
Order By: Relevance
“…(4) Caregiver Abuse Screen (CASE) para rastreamento de violência de cuidadores contra idosos -compõe-se de oito questões, cada uma podendo receber 0 ou 1 ponto, considerando-se risco aumentado de violência uma pontuação a partir de 4. Na presente pesquisa, foi utilizada a versão adaptada para o português 36,37 .…”
Section: Procedimentosunclassified
“…(4) Caregiver Abuse Screen (CASE) para rastreamento de violência de cuidadores contra idosos -compõe-se de oito questões, cada uma podendo receber 0 ou 1 ponto, considerando-se risco aumentado de violência uma pontuação a partir de 4. Na presente pesquisa, foi utilizada a versão adaptada para o português 36,37 .…”
Section: Procedimentosunclassified
“…During the translation of the Brazilian version of the DASI back into English, a number of grammatical changes were necessary. These changes made the items more suitable to Brazilian culture in order to achieve semantic equivalence (between words), idiomatic equivalence (between different idiomatic expressions used in the different cultures), experimental equivalence (words adequate to the cultural context) and conceptual equivalence (validity of the concept explored and events experienced by laypersons) (23,24). Studies have demonstrated that the DASI is correlated with the distance travelled on the Six-Minute Walk Test (r = 0.53) (10), B-type natriuretic peptide levels (r = 0.67) (13), the Canadian Cardiovascular Society Classification (r = 0.58) (7) and patient quality of life and survival (r = 0.64) (11).…”
Section: Resultsmentioning
confidence: 99%
“…The process of semantic assessment is also important because it becomes necessary to make sure that the instrument can be understood by all the members of the target population. 21 Paixão et al 22 highlighted the importance of the translators' profile. According to their guidelines, it is important that the translation process is carried out by professionals whose native language and culture are the same as those into which the scale is being translated.…”
Section: Discussionmentioning
confidence: 99%
“…During the back-translation process, we followed the guidelines of Paixão et al, 22 according to which it is desirable that the translators are familiar with the instrument, the target-population to which the scale is being adapted, as well as its dimensions. The back-translators must receive only limited explanations about the context; therefore, avoiding that they use their previous knowledge to correct occasional mistakes resulting from the initial translation process.…”
Section: Discussionmentioning
confidence: 99%